Association of the consumption of common drinks with early puberty in both sexes - Meng-Che Tsai; Yungling Leo Lee; Yungling Leo Lee; Yungling Leo Lee; Yang Ching Chen; Yang Ching Chen; Yang Ching Chen; Yang Ching Chen (Frontiers Media S.A., 2022)
BackgroundWe examined the effect of sugar-sweetened beverages (SSB) and common drink intake on pubertal development in both sexes.MethodsData were retrieved from Taiwan Children Health Study, which involved detailed pubertal stage assessments of 2,819 schoolchildren aged 11 years in 2011-2012. Drawings of secondary sexual characteristics and self-reported age at menarche or voice breaking were used to assess pubertal stages. Dietary intake was assessed using a detailed semi-quantitative food frequency questionnaire. Generalized estimating equation modeling was applied to obtain odds ratios (ORs) and 95% confidence intervals (CIs) to represent the effects of each drink on early pubertal development outcomes.ResultsIn boys, an one cup/day increment of a SSB was associated with earlier voice breaking (β = −0.12; 95% CI = −0.20, −0.04), whereas consuming yogurt (≥2 cups/day) was a protective factor against early puberty (OR = 0.78; 95% CI = 0.73, 0.83). In girls, SSB consumption was associated with increased risk of early puberty in a dose-response manner, and a similar protective effect of yogurt consumption and fermented probiotic drink (≥2 cups/day) against early puberty was observed (OR = 0.96; 95% CI = 0.94, 0.99). Furthermore, the intake of both total sugar and added sugar within SSBs increased risk of early puberty in girls but not in boys.ConclusionsSugar-sweetened beverages were associated with early puberty, and probiotic drinks appeared to mitigate this link. These findings indicate that the gut-brain axis could play a crucial role in sexual maturation.